2022
DOI: 10.3390/cells11162546
|View full text |Cite
|
Sign up to set email alerts
|

MAGED2 Is Required under Hypoxia for cAMP Signaling by Inhibiting MDM2-Dependent Endocytosis of G-Alpha-S

Abstract: Mutations in MAGED2 cause transient Bartter syndrome characterized by severe renal salt wasting in fetuses and infants, which leads to massive polyhydramnios causing preterm labor, extreme prematurity and perinatal death. Notably, this condition resolves spontaneously in parallel with developmental increase in renal oxygenation. MAGED2 interacts with G-alpha-S (Gαs). Given the role of Gαs in activating adenylyl cyclase at the plasma membrane and consequently generating cAMP to promote renal salt reabsorption v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 54 publications
3
11
0
Order By: Relevance
“…To further support this notion, we also showed that forskolin increases the abundance of MAGED2 transcript under hypoxic conditions, which is in agreement with the presence of four CRE sites in the 2000 bp of the MAGED2 promoter. The lack of effect of isoproterenol in MAGED2-depleted cells on the hypoxic induction of HIF-1α concurs with our previous study showing that MAGED2 is essential for Gαs dependent activation of membrane-bound adenylate cyclase [ 9 ] thereby explaining that agents acting upstream of Gαs such isoproterenol are ineffective in MAGED2-depleted cells.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…To further support this notion, we also showed that forskolin increases the abundance of MAGED2 transcript under hypoxic conditions, which is in agreement with the presence of four CRE sites in the 2000 bp of the MAGED2 promoter. The lack of effect of isoproterenol in MAGED2-depleted cells on the hypoxic induction of HIF-1α concurs with our previous study showing that MAGED2 is essential for Gαs dependent activation of membrane-bound adenylate cyclase [ 9 ] thereby explaining that agents acting upstream of Gαs such isoproterenol are ineffective in MAGED2-depleted cells.…”
Section: Discussionsupporting
confidence: 90%
“…We have shown previously that MAGED2 depletion inhibits the functioning of Gαs by causing its MDM2 and ubiquitin-dependent internalization, which precludes activation of membrane-bound adenylate cyclase and hence cAMP generation [ 9 ]. To investigate if the effects of the MAGED2 knockdown on HIF-1α expression are indeed caused by inhibiting Gαs, we analyzed also the effect of GNAS knockdown on hypoxic HIF-1α induction by exposing cells to physical hypoxia ( Figure 3 a,b) or to the hypoxia mimetic CoCl 2 ( Figure 3 c,d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bartter syndrome is a group of inherited renal tubular diseases characterised by secondary aldosteronism, hypokalaemia and hypochloraemic metabolic alkalosis; blood pressure is not affected ( 4 ). The MAGED2 encodes melanoma-associated antigen D2 (MAGE-D2), required for activation of the cyclic adenosine monophosphate/protein kinase A pathway under hypoxic conditions ( 5 ). MAGE-D2 participates in the biofunction of Na + -K + -2Cl− cotransporters (NKCC2) and Na + -2Cl− cotransporters (NCC), possibly by cooperating with Hsp40 and Gs α proteins, respectively.…”
Section: Discussionmentioning
confidence: 99%